Managing Online Learning : the Life-Cycle of Successful Programs. - Vivolo, John (Routledge, 2019)
Managing Online Learning is a comprehensive guide to planning and executing effective online learning programs. Featuring contributions from experienced professionals across operations in university and corporate settings, this all-in-one resource provides leaders and administrators with informed strategies for supporting learners' and instructors' evolving needs, implementing and evaluating pedagogically sound technologies, projecting revenue-generating models, and anticipating future scaling challenges. These highly applied chapters cover essential topics such as unit design, management of staff and finances, student engagement, user experience and interface, data analytics, and more.- Resumé vydavatel
Keywords: virtuální vzdělávání; vysokoškolské studium; virtual education; college study; elektronické knihy; příručky; electronic books; handbooks and manuals